Penerapan Teknologi Blockchain untuk Memperkuat Privasi dan Keaslian Data Akademik di Perguruan Tinggi - Aurora, Cindy; Henry, Henry; Handra, Tessa; Sutisna, Felix; Parker, Jonathan (Jurnal MENTARI: Manajemen, Pendidikan dan Teknologi Informasi, 2025)
The increasing demand for data integrity and confidentiality in higher education has driven institutions to explore innovative solutions to secure academic records. Traditional database systems often fail to ensure authenticity and protect sensitive information from unauthorized access or manipulation. This study investigates how blockchain technology can enhance privacy and authenticity in university record management. The research uses a descriptive qualitative method with a multiple case study approach. Data were collected through interviews and documentation analysis at selected Indonesian universities piloting blockchain-based systems. The analysis focuses on how blockchain’s decentralized and immutable features support secure data storage, verifiable credentials, and transparent access logs. The findings reveal that blockchain implementation significantly improves trust in academic data by reducing the risk of falsification and enabling real-time validation of records. Moreover, blockchain fosters institutional accountability and streamlines verification processes for both internal and external stakeholders. However, challenges such as integration with legacy systems, technical readiness, and regulatory alignment remain prominent. The study concludes that blockchain offers a promising framework for data-driven management in higher education, particularly in reinforcing the credibility and confidentiality of academic information. The results provide practical insights for policymakers and university leaders seeking to modernize their digital in frastructure while safeguarding the integrity of institutional records.